Anatomical variations: How do surgical and radiology training programs teach and assess them in their training curricula?. Issue 6 (14th May 2015) - Raikos, Athanasios; Smith, Janie Dade
<x xml:space="preserve">Abstract</x> Sound knowledge of anatomy and Anatomical variations plays an integral role in surgical and radiology specialties. This study investigated the current teaching and assessment trends on Anatomical variations in various surgical and radiology specialty training curricula in Canada and Australia. A survey was sent to 122 Program Directors and Chairs of specialty committees in Canada and Directors of Training/Education in Australia of selected surgical and radiology specialties. A total of 80.7% of respondents report that their training curricula include Anatomical variations. The highest rated classes of variations included in the curriculum are arterial (76%), venous (68%), followed by organs (64%). All trainees learn about Anatomical variations from surgeons and radiologists (100%) and via suggested textbooks of the specialty (87.1%). A total of 54.8% report that specialty training curricula do not suggest specific anatomical variation classifications for the trainees to learn, and 16.1% are uncertain if the colleges provide such kind of instruction. Trainees typically communicated findings of variations in case presentations and clinic's meetings. About 32.3% of respondents report that Anatomical variations are not assessed in their training curriculum. About 39.3% of experienced clinicians in the study report they encounter variations on a monthly basis and 25 and 21.4% on a weekly and daily basis, respectively. Surgical and radiology colleges need to investigate for hidden curriculum in their specialty training programs to ensure there are no gaps in knowledge and training related to Anatomical variations. Most educational leaders surveyed believe more teaching on Anatomical variations in the first 4 years of training would benefit resident doctors. Clin. Anat. 28:717–724, 2015. © 2015 Wiley Periodicals, Inc.